Errors in Otolaryngology Revisited. (23rd August 2013) - Shah, Rahul; Boss, Emily F.; Brereton, Jean; Roberson, David W.
Abstract : Objectives: 1) Know the areas of risk for errors in otolaryngology. 2) Be able to discuss the implications of errors in otolaryngology. A decade ago, a survey study of errors in otolaryngology identified areas of risk and proposed a classification schema for errors. This study used a similar methodology to obtain current data for comparison. Methods: An anonymous online survey was distributed via the AAO‐HNS weekly email. Respondents were asked to describe any event in their practice that they felt should not have happened. Events were classified using the prior schema. Results: 445 (66%) of 681 respondents reported an event within the past six months. Mean age of affected patients was 41±24 years. An adverse consequence occurred in over half of events with corrective action taken in 82.8%. 68% of respondents subsequently changed their practice patterns. Domains with the most reported errors were technical (27.9% of all events, 71% with major morbidity), administrative (12.2%, 3.7%), errors in testing (10.8%, 8.3%), and surgical planning (9.9%, 45.5%). There were 8 wrong site surgeries, 23 cranial nerve injuries (91.3% major morbidity), and 9 errors during endoscopic sinus surgery (55.6% major morbidity). There were 4 deaths. Conclusions: Otolaryngologists remain vulnerable to error‐related adverse events. The domains with the greatest risk for error‐related major morbidity have changed little and include errors in surgical planning, equipment‐related errors, and technical errors (surgery near cranial nerves and endoscopic sinus surgery). Awareness of high‐risk areas may help us focus more preventive efforts in these domains.